Assessment of the Periodontal Parameters in Pregnant Women Diagnosed with Metabolic Syndrome: A Cross-Sectional Study - Ghousia Sayeed; Sheeja S. Varghese (Journal of Pharmacy and Bioallied Sciences)
Background: The prevalence of metabolic syndrome (MeS) is increasing due to modern lifestyles, making it essential to explore its connection with conditions like periodontitis, particularly in pregnant women. This study aims to evaluate the periodontal parameters health of pregnant women with metabolic syndrome. Material and Methods: The study included 144 pregnant women aged 18–34 with MeS. Demographic data collected encompassed age, nutrition, medical history, and oral health practices. Dental exams assessed the gingival index, plaque index, bleeding on probing, probing depth, and clinical attachment loss, classifying participants into mild, moderate, and severe periodontitis. Blood glucose, triglycerides, HDL cholesterol, systolic and diastolic blood pressure, waist circumference, and BMI were measured to analyze the relationship between the number of MeS components and periodontal disease severity using a Chi-square test. A P value of less than 0.05 was considered statistically significant. Results: Gingivitis was present in 33.3% of the subjects, whereas severe periodontitis was in 20.8%. Nonetheless, there was no discernible correlation (P > 0.05) between periodontal disease severity and MeS risk variables. Conclusion: The majority of subjects had gingivitis, although all patients with MeS exhibited periodontal disease to some degree. However, there is still debate over whether or whether an increased presence of MeS components is associated with more severe periodontal disease, particularly during pregnancy.